2018
DOI: 10.4314/ovj.v7i4.15
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic activity on wild animals through the description of a model case report (caseous lymphadenitis by <i>Corynebacterium pseudotuberculosis</i> associated with <i>Pasteurella</i> spp and parasites infection in an alpine ibex –<i>Capra ibex</i>)

Abstract: The diagnostic activity on wild animals implies a hard laboratory protocol where multiple disciplines, from biology to pathological anatomy until the biotechnological techniques, must be integrated to establish the causes of death. To demonstrate these concepts, the analytical approach adopted for an alpine ibex (Capra ibex) found dead in a mountain area of North Western Italy was described. The animal showed sub-costal and lymph nodes collections of greenyellow pus, fibrinous pleuropneumonia and catarrhal-hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Wild Caprinae species have been reported to be infected with CLA; for example, a captive population of Iberian Ibex in Spain showed a 19% positivity rate for C. pseudotuberculosis antibodies [26]. An Italian case study of CLA in Alpine Ibex with purulent collections in various lymph node groups (in particular, subcutaneous and mediastinal) [27] was followed by a comprehensive survey of 98 alpine chamois, which thoroughly described the disease in many different aspects [28]. Domenis et al (2018) [28] describe four different gross lesion distribution patterns, observed individually or variably combined in the same animal (cutaneous/external, abdominal visceral, thoracic visceral and generalized visceral).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild Caprinae species have been reported to be infected with CLA; for example, a captive population of Iberian Ibex in Spain showed a 19% positivity rate for C. pseudotuberculosis antibodies [26]. An Italian case study of CLA in Alpine Ibex with purulent collections in various lymph node groups (in particular, subcutaneous and mediastinal) [27] was followed by a comprehensive survey of 98 alpine chamois, which thoroughly described the disease in many different aspects [28]. Domenis et al (2018) [28] describe four different gross lesion distribution patterns, observed individually or variably combined in the same animal (cutaneous/external, abdominal visceral, thoracic visceral and generalized visceral).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence of CLA or C. pseudotuberculosis infections has been reported in other wildlife species, mainly ruminants: cervids, wild caprinae species and antelopes [25]. The majority of research has focused on wild caprinae, with numerous samples being analyzed [26][27][28]. On the other hand, the limited number of cervid studies counted few animals, describing both forms of CLA attributable to C. pseudotuberculosis [29][30][31][32][33] and extremely similar C. ulcerans infections [5].…”
Section: Introductionmentioning
confidence: 99%